Challenges of safeguarding via remote consulting during the COVID-19 pandemic: a qualitative interview study - Dixon, S; Frost, L; Feder, G; Ziebland, S; Pope, C (Royal College of General Practitioners, 2022)
Background The COVID-19 pandemic required general practice to rapidly adapt to remote consultations and assessment of patients, creating new, and exacerbating existing, vulnerabilities for many patients. Aim To explore GP perspectives and concerns about safeguarding practice during the pandemic, focusing on challenges and opportunities created by remote consultation. Design and setting Qualitative interview study. Method Eighteen GPs from Oxford, London, Southampton, Liverpool, Manchester, and Reading were interviewed between June and November 2020, using a flexible topic guide and fictional vignettes to explore child and adult safeguarding scenarios. Interviews were audio-recorded, thematically coded, and analysed. Results GPs worried about missing observational information during remote consultations and that conversations might not be private or safe. Loss of continuity and pooled triage lists were seen as further weakening safeguarding opportunities. GPs experienced remote consulting as more ‘transactional’, with reduced opportunities to explore ‘other reasons’ including new safeguarding needs. However, they also recognised that remote consulting created opportunities for some vulnerable patients. While supporting known vulnerable patients was difficult, identifying new or unknown vulnerabilities was harder still. Most reported that remote consulting during COVID-19 was harder, riskier, and emotionally draining, contributing to increased GP anxiety and reduced job satisfaction. Conclusion The GPs interviewed raised important concerns about how to identify and manage safeguarding in the context of remote consultations. Current guidance recommends face-to-face consultation for safeguarding concerns, but pressure to use remote forms of access (within or beyond the pandemic) and the fact that safeguarding needs may be unknown makes this an issue that warrants urgent attention.